2020
DOI: 10.1021/acs.jafc.0c06244
|View full text |Cite
|
Sign up to set email alerts
|

Comparative Evaluation of Key Aroma-Active Compounds in Sweet Osmanthus (Osmanthus fragrans Lour.) with Different Enzymatic Treatments

Abstract: Sweet osmanthus (Osmanthus fragrans Lour.) (OF) is one of the ten most famous flowers in China for its unique and delicate fragrance. A combined solid-phase microextraction and solvent-assisted flavor evaporation method was used to accurately capture the overall aromatic profile and characterize the predominant odorants of fresh osmanthus with the help of gas chromatography (GC)–olfactometry and comprehensive two-dimensional GC–quadrupole time-of-flight mass spectrometry (GC × GC–QTOF–MS). Twenty-six volatiles… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
11
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 22 publications
(13 citation statements)
references
References 44 publications
1
11
0
Order By: Relevance
“…Among them, 73 and 39 aroma compounds were extracted by HS-SPME and SAFE, and 26 aroma compounds were detected by both two methods. Consistent with the results of Niu et al 52 and Sheng et al, 14 the number of aroma compounds extracted by both HS-SPME and SAFE was small, which indicated that the use of multiple extraction methods allowed for a more comprehensive profiling of the sample aroma. Standard curves were established for 86 compounds to calculate their concentration.…”
Section: ■ Results and Discussionsupporting
confidence: 86%
See 1 more Smart Citation
“…Among them, 73 and 39 aroma compounds were extracted by HS-SPME and SAFE, and 26 aroma compounds were detected by both two methods. Consistent with the results of Niu et al 52 and Sheng et al, 14 the number of aroma compounds extracted by both HS-SPME and SAFE was small, which indicated that the use of multiple extraction methods allowed for a more comprehensive profiling of the sample aroma. Standard curves were established for 86 compounds to calculate their concentration.…”
Section: ■ Results and Discussionsupporting
confidence: 86%
“…The solvent-assisted flavor evaporation (SAFE) extracts volatile compounds in a low-temperature and high-vacuum environment, which is a mild pre-treatment method and can avoid the effect of the matrix. Among them, SPME is effective in trapping highly volatile compounds, and SAFE is suitable for extracting high boiling point compounds in complex matrices. The combination of SPME and SAFE has been shown to provide comprehensive aroma characterization of samples such as potato snacks, apple cider, watermelon juice, Sachima, and red raspberry juice …”
Section: Introductionmentioning
confidence: 99%
“…HDO showed significant differences in both green and sweet, which might be the higher concentration in MH and OM groups. Linalool, an aroma compound with a green and bois de rose smell, was the main aroma compound of HDO with high aroma intensity [1] . UFEO was stronger in the characteristic aroma of osmanthus, which is more floral, fruity, and sweet, and has a lower green aroma.…”
Section: Resultsmentioning
confidence: 99%
“…β‐ionone, dihydro‐β‐ionone, linalool, and linalool oxide were the main volatile compounds of osmanthus [2] . Recent research on volatile compounds of osmanthus was based on HS‐SPME on fresh flowers or the essential oil from hydrodistillation [1,7,8] . Meanwhile, the different extraction methods would lead to different aroma and biological activities since the constituent of compounds [2,9,10] .…”
Section: Introductionmentioning
confidence: 99%
“…An eQTL (9_19892312 bp) from chromosome 9 located in intergenic region of two β -glucosidase genes (Os09g0511700 and Os09g0511600) had significant effects on BADH2 expression . Glucosidase enzymes hydrolyze glycosides and release aromatic components with a natural flavor [40] .
Fig.
…”
Section: Resultsmentioning
confidence: 99%